Vital NETosis vs. suicidal NETosis during normal pregnancy and preeclampsia - Guillotin, Florence; Fortier, Mathieu; Portes, Marie; Demattei, Christophe; Mousty, Eve; Nouvellon, Eva; Mercier, Eric; Chea, Mathias; Letouzey, Vincent; Gris, Jean-Christophe; Bouvier, Sylvie (Frontiers in Cell and Developmental Biology, 2023)
Background: NETosis occurs in the context of infection or inflammation and results in the expulsion of decondensed DNA filaments called NETs (Neutrophil Extracellular Traps) into the extracellular environment. NETosis activates coagulation and contributes to the thrombotic risk of inflammatory diseases. To date, two mechanisms of NETosis have been identified: suicidal NETosis, in which neutrophils die after expelling the filaments; and vital NETosis, in which expulsion appears without altering the membrane. Human pregnancy is associated with a mild pro-inflammatory state, which is increased in the event of complications such as preeclampsia (PE). NETosis has been observed in these situations, but the mechanism of its production has not yet been studied. Objectives: The aim of our study was to evaluate the balance of vital vs. suicidal NETosis in normal pregnancy and in PE. Patients/Methods: Neutrophils from healthy volunteers were stimulated with plasma from normal pregnancies (n=13) and from women developing preeclampsia (n=13). Immunofluorescent labelling was performed to determine the percentages and origin of NETs in both groups. Inhibition with suicidal or vital NETosis inhibitors was also performed to validate our results. Results: We found a significant increase in NETs in women with PE compared to women with normal pregnancies. We showed that vital and non-vital NETosis are present in normal and preeclamptic pregnancies. We demonstrated that the higher proportion of NETs observed in PE was due to non-vital NETosis whose main component is represented by suicidal NETosis. Conclusion: These results suggest the important part of non-vital NETosis in the pathophysiology of PE.